Formulation and characterization of halal palm-based shortening in simulating lard properties for food industry - Mohamed Roslan, Nur Illiyin (2020)
Shortening is a commercially prepared edible fat that is primarily used in the cooking and baking of food. The function is to ‘shorten’ or tenderize food; especially baked goods. Shortening is formulated 100% from either animal fat and/or vegetable fat. Plant-based fats, such as palm oil and its fraction, can substitute the use of animal fat such as lard as the source of shortening. Lard which is traditionally used as shortening, however, has the limitation due to the teaching of Islam that prohibits the consumption of it and the derivatives. Besides that, there is a growing negative perception of animal fats and their implications on human health among the consumer as well. Many halal shortenings can be found easily in the market. Usually, the formulation involved vegetable oils such as palm oil, soybean, canola oil, and olive oil. However, the compatibility of those halal shortening to lard in terms of their quality is scarcely found. Besides, the study of the development of halal shortening tends to simulate lard properties is still limited. Thus, this present study covers the formulation of halal palm-based shortening by using mixture design as the tool of optimization in simulating lard properties. The formulation is comprising of a combination of palm oil (PO), palm olein (POO60), palm mid fraction (PMF), and soybean oil (SB). The selected formulations were further characterized in terms of physicochemical properties such as hardness, microstructure, thermal behaviour, fatty acid content (FAC), triacylglycerol (TAG), and polymorphism. The effect of the emulsifier on the physicochemical properties of the palm-based shortenings has also been investigated. The application of the palm-based shortenings was done in dough and cookies preparation to compare the performance between those made out from palm-based shortening and those of lard. The optimization of palm-based shortening involved two responses which were slip melting point (SMP) and solid fat content (SFC). The analysis of variance expressed the precision of the special cubic model for SMP, employing high F-value (27.73), low P-value (<0.0001), and R-squared (0.9541) with insignificant lack-of-fit. Meanwhile, the linear model for SFC indicated a high F-value (103.87), low P-value (<0.0001), and R-squared (0.9432) with insignificant lack-of-fit. The effect of the three combinations of variables was also investigated, in which the palm oil had contributed to give a positive effect to the blends in both responses (SMP and SFC). The formulated palm-based shortening was found similar in terms of the slip melting point and the solid fat content as lard in the portion of PMF: PO: SB: POO60 (10.00:35.18:34.82:20.00) (PO: SB: POO60). In the comparison to lard, the most similar shortening namely F14 (10.00: 35.18: 34.82: 20.00) was further characterized with another shortening namely F9 (10.00: 39.99: 30.01: 20.00) which contained the highest palm oil portion in the formulated blends. The characterization involved hardness, microstructure, thermal behaviour, fatty acid content, triacylglycerol, and polymorphism. The total amount of saturated fatty acid in the prepared shortening was comparable to lard; (F9 and F14; 39.44 % and 37.83 % respectively) and lard was 36.43 %. It was also found that the blend of F9 and F14 possessed the amount of oleic acid with 35.63 % and 34.95 % in which are close to the amount of lard (39.23 %). Similarly, the content of linoleic acid displayed the comparable content of fatty acid composition with lard (20.7 %) which was 22.84 % and 24.97 % for the blends of F9 and F14, respectively. The hardness of the prepared shortenings was found higher than lard. The microstructure of the palm-based shortening was found better-arranged and smaller as compared to lard. The TAG molecular groups of PLO and POO were found dominant in the prepared shortening as well in lard. Thermal behaviour of the prepared shortening was found similar to lard with melting range temperature at 0-1°C. Polymorphic form of the palm-based shortening was similar to lard which was in β’+β form. The next chapter demonstrated the effect of emulsifier on the formulated palm-based shortening in simulating lard properties. F14 shortening remained to have the hardness closest to lard. From the microscopic view, the incorporation of emulsifier in the shortening exhibited a more arranged fat crystal and showed the dissimilarities to lard. There were no significant changes as the addition of emulsifier in the shortening on the fatty acid content and TAG distribution. the high melting peak of F903 shortening (C6:31.89 ºC) was found to have the closest to the high melting peak of lard which was at (A3: 29.62 ºC). The polymorphic crystal forms of all samples were similar to that of lard with a mixture of β’ and β crystal form. The formulations were applied in cookie making in the next chapter. The dough and cookies that were prepared from palm-based shortenings were compared to those prepared from lard. the dough prepared from F141 shortening was found similar to the dough which was prepared from lard in terms of hardness which was 16.16 N and 11.77 N respectively. The dough prepared from lard, F9, F14, and F141 showed insignificant elasticity behaviour. The tan δ values of F14, F9, F141 were very similar to lard, which are 0.56, 0.54, 0.56, respectively, as compared to lard (0.55). The thickness of the cookies made out of F903 (6.2 mm) showed a similar thickness as the cookies made out of lard (6.2 mm). Besides that, cookies containing dough F1403 (0.7 mm) and F141 (0.7 mm) were found to have a similar width to the cookies containing lard (0.7 mm). Meanwhile, the spread ratio of the cookies prepared from F9 (9.6), F14 (9.4) and F141 (9.5) exhibited a similar value to those made from lard (9.6). The cookies that containing F14 shortening, showed the most similar value of a* and b* (6.47, 29.7) to the lard-based cookie (6.40, 26.47). In this present study, the palm-based shortening is comparable to traditional shortening such as lard. Thus, this could be a useful finding in improving the formulation of halal shortening that tends to simulate lard properties.